Impact of the Coronavirus (COVID-19) pandemic on sexual and reproductive health in Latin America: Literature review. - sánchez-Broncano, Junior Duberli (2023)
Introduction. The need for good sexual and reproductive health (SRH) is inherent to all individuals, impacting public health indicators and requiring attention from global health policies, especially during the COVID-19 pandemic, where access to healthcare services has been limited and its impact is still unknown. Objective. To review the impact of the COVID-19 pandemic on sexual and reproductive health in Latin America. Materials and Methods. Qualitative study, descriptive level, and documentary design based on a systematic review of literature in databases (Scielo, Virtual Health Library, PubMed, Wiley Online Library, Redalyc, ScienceDirect, and MDIP) published in Latin America in three languages (Spanish, English, and Portuguese). A sample of 21 out of 1316 articles was obtained after two stages: advanced search with an algorithm and initial filtering, and second stage of full-text review. The data extraction form and content analysis were used as instruments. Results. The highest scientific production in SRH was found in Brazil and Colombia. COVID-19 has resulted in a deficit in access to SRH services, especially for Venezuelan migrants, sex workers, and women with hearing disabilities. More than 50.0% of men who have sex with men (MSM), transgender and gender non-binary individuals (TGNB), and HIV-infected individuals have discontinued antiretroviral therapy (ART) and screening tests. An increase in the use of technological tools has been reported as a strategy to address coverage and access to SRH services without exclusion. Conclusions. COVID-19 has had unfavorable effects on SRH services, limiting access to HIV/STI testing and follow-up, ART delivery, and distribution of contraceptives among vulnerable populations such as immigrants, LGBT+ individuals, and sex workers.